A probable non-annelid origin of pods attached to Amaeana ellobophora (Annelida: Polycirridae) - Read, Geoffrey B.; Nogueira, João Miguel De Matos (Zootaxa, 2015)
There is an alternative explanation to the proposal by Nogueira et al. (2015) that the polycirrid Amaeana ellobophora Nogueira, Carrerette & Hutchings, 2015 is a species which broods eggs in attached cocoons. We suggest that the pods observed fixed to the anterior of one worm are instead highly modified parasitic copepods (Arthropoda: Crustacea: Copepoda: Poecilostomatoida), and thus do not provide any information on the reproductive mode of Amaeana Hartman species.